Given differential equation "(D^3-1)y=sinx"
Auxiliary equation corresponding to the given homogeneous differential equation is
"m^3-1=0\\Rightarrow (m-1)(m^2+m+1)=0"
"\\Rightarrow m=1,m=\\frac{-1\\pm \\sqrt{1-4}}{2}=\\frac{-1\\pm \\sqrt{3}i}{2}"
Solution to the homogeneous differential equation is
"y_{h}(x)=c_{1}e^{x}+e^{\\frac{-x}{2}}\\left [ c_{2}cos(\\frac{\\sqrt{3}x}{2})+c_{3}sin(\\frac{\\sqrt{3}x}{2}) \\right ]"
Now let us find the particular solution using the method of undetermined coefficeints.
A particular solution using the method of undetermined coefficients is
"y_{p}(x)=Asinx+Bcosx"
"\\Rightarrow y'_{p}(x)=Acosx-Bsinx, y''_{p}(x)=-Asinx-Bcosx,"
"y'''_{p}(x)=-Acosx+Bsinx"
Now "y'''_{p}(x)-y_{p}(x)=sinx"
"\\Rightarrow -Acosx+Bsinx-Acosx+Bsinx=sinx"
"\\Rightarrow -2Acosx+2Bsinx=sinx"
"\\Rightarrow A=0, B=\\frac{1}{2}"
So, the particular solution is "y_{p}(x)=\\frac{1}{2}cosx"
Therefore, general solution to the given differential equation is
"y(x)=y_{h}(x)+y_{p}(x)"
That is
"y(x)=c_{1}e^{x}+e^{\\frac{x}{2}}\\left [ c_{2}cos(\\frac{\\sqrt{3}x}{2})+c_{3}sin(\\frac{\\sqrt{3}x}{2}) \\right ]" "+\\frac{1}{2}cosx"
Comments
Leave a comment